Synthesis a nd Characterization of Some New Transition Metal Complexes of Amino Thiadiazole - Numan, A.T; Jassim, l.Kh; Issa, l.O (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
New complcxcof        Cu (ll),Ni(ll)  ,Co(ll),  and Zn(ll)  wi th 2- amino-5-p-Fiouro Phenyl 1,3,4-Thiadiazole  have been synthesized  . The  products  were isolated , studied  and characterized by physical measurements, i.e., (Ff -IR) ,UV-Vis and  the melting points were determined .The new Schiff base (L) has been used to prepare some complexes  .The   prepared  complexes  were   identified  and   their tructural geometry were suggested.